Optimization of Physico-Chemical Parameters for Hyper Keratinase Production from a Newly Isolated Aspergillus sp. DHE7 using Chicken Feather as Substrate- Management of Biowaste - Dina Helmy El-Ghonemy, Thanaa Hamed Ali (Journal of Applied Pharmaceutical Science, 2017)
Keratinases have recently gained biotechnological impetus due to their ability in degrading insoluble keratinous solid wastes into simplified forms, which used in the preparation of nitrogenous fertilizers, biodegradable films, glues and foils. Keratinases are widespread in nature and mainly produced by diverse microorganisms including bacteria, fungi and actinomycetes. Therefore, the aim of the present work was to isolate and identify a new potent fungal strain possessing extracellular keratinase production capacity using keratinous solid wastes as the sole carbon and nitrogen sources. Fifteen keratinolytic fungi, isolated from a poultry farm soil using white chicken feathers as substrate, were screened qualitatively and quantitatively for their ability to produce extracellular keratinase. Medium optimization for enzyme production was also studied under submerged fermentation conditions. The results revealed that a new fungus identified as Aspergillus sp. DHE7 was reported as the most potent fungal strain for extracellular keratinase production under submerged shaking conditions (120 rpm). The highest yield of enzyme of 199+4.2 U/mL was observed after four days of incubation at pH 6.0 and temperature 30 °C using 2 % of chicken feathers as substrate. Medium supplementation with 0.5 % sucrose as an additional source of carbon increased keratinase yield to 226+5.4 U/mL. While using additional nitrogen sources could not promote a favorable effect on keratinase productivity as compared with the basal medium. Different keratinous wastes were used as substrate in the basal medium and better keratinase production was obtained with goat hair medium (452+12.3 U/mL) followed by turkey feather (435+9.2 U/mL) and sheep wool (322+13.4 U/mL) media. The present data suggest Aspergillus sp. DHE7 as a potential keratinolytic strain for the bioconversion of keratinous wastes, through a non-polluting process.
Keywords: Keratinase, Aspergillus sp. DHE 7,optimization, keratinous wastes, biowaste management.